PENGEMBANGAN BAHAN AJAR MATA KULIAH ALJABAR LINEAR BERBASIS OPEN ENDED - Farida, Nurul; Suryadinata, Nurain (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
Teaching materials is one important component in learning because teaching materials can be used for independent study. On the other hand, the lack of teaching materials are on open-ended problems leads to an underdevelopment of creativity in learning. With the open-ended problems, students are expected to have more than one solution to solve problems in everyday life, especially in mathematical problem solving. The purpose of this study is to develop teaching materials based on open-ended valildly, practically and effectively in the subject of linear algebra. This research is the development by using Plomp models which consists of three stages: preliminary research, prototyping, and assessment. Data collection technique through observation, questionnaires and tests. The instruments used were observation sheet, questionnaire sheet and a test sheet. Based on result of the research that has been done shows that the teaching materials is based on open-ended in the subject linear algebra that have been developed otherwise valid with a value of 3.43, practice with a value 3,11 or in the percentage reached 77,75%, and effective with value of learning outcomes experiment class (use teaching materials developed) higher than control class.